Stigmast-5(6)-en-3(6)-ol dari Herba Tumbuhan Krokot (Lygodium microphyllum) - Hadi Kuncoro; Kindi Farabi; Euis Julaeha; Laode Rijai; Unang Supratman (Syarif Hidayatullah State Islamic University, 2015)
A steroid, stigma-5(6)-en-3β-ol or β-sitosterol (1) had been isolated from a n-hexane extract of the Krokot plant herb (Lygodium microphyllum). The chemical structure of 1 was identified on the basis of spectroscopic evidences and by comparison with those of spectra data previously reported. The investigation of steroid, stigma-5(6)-en-3β-ol was from L. microphyllum plant was reported inthis research for first time.DOI :http://dx.doi.org/10.15408/jkv.v0i0.3152